Development Of Integrated 3-Dimensional And Virtual Reality Digital Outcrop Model Of Sedimentary Rock Slope - Allias, Muhammad Afiq Na’imullah (Universiti Sains Malaysia, 2022)
During this Fourth Industrial Revolution (IR 4.0) where the advancement in technology is at its peak, some things just becoming to get much easier and simpler. By implementing aerial photogrammetry techniques with the aid of Unmanned Aerial Vehicles (UAVs), specifically using DJI Phantom 4 Pro drone, a 3-dimensional digital outcrop model could be generated by your fingertips. The digital outcrop model would then be evaluated to gather geological characteristics of the rock slope outcrop using the conventional geological mapping technique and 3D model. In this study, 3D digital outcrop models are developed using drone mapping softwares and the output will be further analyze using geological softwares such as Virtual Reality Geological Studio (VRGS) Software to digitally evaluate and do some geological interpretations of the rock slope outcrop models. For geologists and rock engineers, digital photogrammetry is a helpful tool in remote characterisation technique where there may be some limitations and difficulties for a physical discontinuities evaluations to be done. Data collection method and its accuracy from conventional fieldwork may also not sufficient enough due to previous limitations plus conventional fieldwork may be time and energy consumption to be done. Comparison about the capabilities and limitations between the digital analysis data and conventional fieldwork data will be explained during this study and also the limitations of each individual softwares used in obtaining the nature of discontinuities of a rock mass. Kinematic stability using stereonet will be further explained to determine the possible failure types of the real rock slope outcrop site.